The Pathology Lesion Patterns of Podocytopathies: How and why? - Ravaglia, Fiammetta; Melica, Maria Elena; Angelotti, Maria Lucia; De Chiara, Letizia; Romagnani, Paola; Lasagni, Laura (Frontiers in Cell and Developmental Biology, 2022)
Podocytopathies are a group of proteinuric glomerular disorders driven by primary podocyte injury that are associated with a set of lesion patterns observed on kidney biopsy, i.e., minimal changes, focal segmental glomerulosclerosis, diffuse mesangial sclerosis and collapsing glomerulopathy. These unspecific lesion patterns have long been considered as independent disease entities. By contrast, recent evidence from genetics and experimental studies demonstrated that they represent signs of repeated injury and repair attempts. These ongoing processes depend on the type, length, and severity of podocyte injury, as well as on the ability of parietal epithelial cells to drive repair. In this review, we discuss the main pathology patterns of podocytopathies with a focus on the cellular and molecular response of podocytes and parietal epithelial cells with the aim to suggest a revision of the current diagnostic and therapeutic management of podocytopathies.